Temperature and atmosphere composition influence on colour change of apples : a dissertation presented in partial fulfilment of the requirements for a Masterate of Horticultural Science, Massey University, Palmerston North, New Zealand - Dixon, Jonathan (Massey University, 1993)
In apples colour is a major quality parameter used by consumers to determine apple maturity. A full understanding of the nature of the relationship between storage conditions and apple fruit colour change would be of advantage in formulating models to predict how changes to handling systems would affect fruit colour. While much is known in a general way about how environmental conditions affect colour change, little information is available to characterise the nature of the relationships between temperature, oxygen and carbon dioxide. The postharvest change in colour was measured for two export apple cultivars; Cox's Orange Pippin and Granny Smith. Previous research on these and other apple cultivars has determined that colour change is from green to yellow. The colour of Cox's Orange Pippin and Granny Smith apples were measured by subjective and objective methods during experiments to investigate the effect of temperature and atmosphere composition on colour change. The objective methods used were: chlorophyll extraction and colour using a Minolta chromameter. The subjective method was colour matching for Granny Smith using the NZAPMB maturity colour charts. When related to changes in chlorophyll, the principal skin pigment, the colour parameters used had non-linear relationships. Lightness, hue angle and colour chart score all reflect pigment changes occurring as apples change colour from green to yellow. Lightness values were the least variable followed by hue angle then colour chart score. All methods used showed more sensitivity to changes in chlorophyll content when chlorophyll content was low compared to when chlorophyll content was high. The objective measurements were highly correlated with the subjective measurements and the conclusion was that the use of hue angle or lightness to follow colour change in the skin of Granny Smith and Cox's Orange Pippin apples is an accurate indirect measure of chlorophyll and other pigments. The rate constant of colour change (k), measured using a declining exponential function, from green to yellow, at eleven temperatures over two seasons, two harvests per season and several growers was investigated in order to characterise the relationship between yellowing and temperature. All the methods of colour measurement used had the same relationship with temperature which was described by a modified form of the Arrenhius equation. Re-worked published data also fitted the modified Arrenhius equation. The modified Arrenhius equation was used to generate k for the various colour parameters measured (chlorophyll, hue angle, lightness and colour charts score). The value of k, as a function of temperature, increases slowly between 0°C and 6°C (the lag phase), increases exponentially between 6°C and 20°c and reaches a maximum at 25.3°C for Cox's Orange Pippin and 23.5°C for Granny Smith before declining. Pattern of response to temperature was the same for each cultivar although Granny Smith yellowed more slowly than Cox's Orange Pippin. For Cox's Orange Pippin apples more variation was accounted for by differences between growers than years or harvests within a year. For Granny Smith fruit most variation was accounted for by differences between years. Sixteen atmospheres were used each year for Cox's Orange Pippin and Granny Smith apples from one harvest in order to characterise the relationship between yellowing and oxygen or carbon dioxide. Cox's Orange Pippin and Granny Smith apples differ in their response to oxygen. For Cox's Orange Pippin the value of k as a function of oxygen level increased slowly from 0% to 6% and thereafter increased exponentially from 6% to 19%. This function may be sigmoidal as the k values increase slows above 17% oxygen. The relationship for Granny Smith was poorly defined by this function, k values increased slowly as the oxygen level rose. This could be due to a fundamental physiological or biochemical difference between these two cultivars. Each cultivar had a similar response to carbon dioxide, described by a declining exponential function, with the relationship for Granny Smith being better defined than for Cox's Orange Pippin. The relationship of carbon dioxide with colour change was poorly defined as the effects of oxygen on colour change were not removed from the analysis. Oxygen appears to have a greater influence on colour change than carbon dioxide. Atmospheres for Cox's Orange Pippin apples were not scrubbed for carbon dioxide in 1989 but were in 1990. The pattern of response to oxygen in the absence of levels of carbon dioxide above 1% in the atmosphere did not alter the sigmoidal relationship found. This may be evidence that the effect on yellowing by oxygen and carbon dioxide is by separate processes. Ethylene levels in the atmosphere appeared to have little effect on the rate of yellowing in all the atmospheres studied. The carbon dioxide and oxygen functions were combined into a single equation for use as a predictive model. The temperature function, the modified Arrenhius equation, and the atmosphere functions were combined into one equation to which different environmental values were added. The use of such a model and other practical applications for the information gathered for this thesis are discussed and a chart drawn comparing the hue angle, lightness and colour chart score to chlorophyll level.
Keywords: Apples; Storage; Standards; 300802 Horticultural crop growth and development